Federated Multimodal Learning for Predicting HIV Care Retention and Viral Suppression: Integrating EHR Phenotypes, Social Determinants of Health, and Explainable AI - Petri D. Jones; Anand Brivastava; Xavier Howard (International Journal of Clinical and Translational Medicine, 2026)
The HIV care continuum remains marked by persistent disparities in retention and viral suppression, particularly among marginalized populations where structural barriers intersect with clinical phenotypes. Existing predictive models often rely on centralized electronic health record data, which raises privacy concerns, fails to capture social determinants of health at scale, and lacks the transparency needed for clinical adoption. This paper proposes a federated multimodal learning framework that integrates structured EHR phenotypes with geocoded and survey-based social determinants of health while embedding explainable artificial intelligence techniques to ensure model interpretability. We examine the architectural trade-offs inherent in federated learning for heterogeneous health data sources, including communication efficiency, non-IID data distributions, and differential privacy budgets. The framework further incorporates fairness-aware aggregation to mitigate biases that could propagate health inequities. We discuss infrastructure requirements for deployment across safety-net clinics and public health agencies, emphasizing sustainability through continuous learning and model governance. The integration of explainability methods such as feature attribution and counterfactual reasoning enables clinicians and policymakers to interrogate predictions and intervene appropriately. Through a comparative analysis of centralized, federated, and hybrid architectures, we demonstrate that federated multimodal learning can achieve comparable predictive performance while preserving data sovereignty and providing actionable insights. Policy implications for data sharing, consent models, and regulatory oversight are considered. This work contributes a systems-level design for ethically responsible, privacy-preserving, and interpretable machine learning in HIV care.